2021
DOI: 10.3390/ijms22041884
|View full text |Cite
|
Sign up to set email alerts
|

Strong Dependence between Tryptophan-Related Fluorescence of Urine and Malignant Melanoma

Abstract: Urine autofluorescence at 295 nm is significantly higher in patients with malignant melanoma at each clinical stage compared to the healthy group. The largest difference is in the early-stages and without metastases. With increasing stage, the autofluorescence at 295 nm decreases. There is also a significant negative correlation between autofluorescence and Clark classification. Based on our results, it is assumed that the way malignant melanoma grows also affects urinary autofluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Sári et al pointed to the cytostatic properties of indoxyl sulfate, a bacterial metabolite of Trp, in breast cancer [ 39 ]. Recent studies have shown increased urinary IS concentrations in melanoma patients [ 4 , 5 ]. In our previous study, we pointed to a correlation between DHICA, Trp, and IS urinary excretions in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sári et al pointed to the cytostatic properties of indoxyl sulfate, a bacterial metabolite of Trp, in breast cancer [ 39 ]. Recent studies have shown increased urinary IS concentrations in melanoma patients [ 4 , 5 ]. In our previous study, we pointed to a correlation between DHICA, Trp, and IS urinary excretions in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…As an essential amino acid, it is mostly taken up by nutrition and is metabolized via three pathways: the kynurenine, serotonin, and indole pathways in mammalian cells ( Figure 1 ). In addition to tyrosine, tryptophan and its metabolites are also involved in melanogenesis [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 3D fluorescence analysis in both applications, EEM or CW, has been successfully used for the study of various types of biological materials, such as tissues [2, 5-7, 12, 13], cells [14][15][16], blood serum [17][18][19][20][21][22] and urine [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…uFCMatrix provides an idea of the composition, the initial concentration of the urine sample, and the amount of water contained [26,27]. Kollarik et al [34] applied uFCMatrix to analyze urologic patients, and Birková et al to characterize the urine of patients with malignant melanoma [31]. The application of uFCMatrix also inspired Martinicky et al [33] in screening female patients with ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue contains seven reviews and nine original research articles that conclusively demonstrate developmental programming and reprogramming [ 1 ], uniqueness of tryptophan [ 2 ], the role of 5-hydroxytryptophan [ 3 ], tryptophan AhR-ligands in the skin [ 4 ], the impacts of tryptophan metabolites on coronavirus pathophysiology [ 5 ], tryptophan metabolism in organ transplantation [ 6 ], gut-derived 5-hydroxytryptamin [ 7 ], effects of AhR-ligands on melanoma cells [ 8 ], effects of stress and escitalopram on genes of the tryptophan catabolite pathways [ 9 ], formation of tryptophan derivatives by Saccharomyces cerevisiae [ 10 ], the relationship between tryptophan-related fluorescence in urine and malignant melanoma [ 11 ], the effects of tryptophan supplementation on milk protein synthesis and energy metabolism [ 12 ], the induction of tryptophan deficiency and dysbiosis with associated increased systemic inflammation in aged mice [ 13 ], the effects of tyrosine and tryptophan supplementation on diet-induced obesity [ 14 ], degradation products of tryptophan [ 15 ], and the molecular interactions of nitrofurantoin and albumin [ 16 ].…”
mentioning
confidence: 99%